2015
DOI: 10.48550/arxiv.1510.01950
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kepler Eclipsing Binaries with Stellar Companions

Abstract: Many short-period binary stars have distant orbiting companions that have played a role in driving the binary components into close separation. Indirect detection of a tertiary star is possible by measuring apparent changes in eclipse times of eclipsing binaries as the binary orbits the common center of mass. Here we present an analysis of the eclipse timings of 41 eclipsing binaries observed throughout the NASA Kepler mission of long duration and precise photometry. This subset of binaries is characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In such a case, it is possible that there is a long-period third star in the system causing the periodic variations of their orbital periods. For example, Gies et al (2015) have found several detached eclipsing binaries in the Kepler field where the mass transfer process can be rejected due to their detached configurations, so a tertiary companion is the cause of the variations. However, if the orbital period of the third star is very long, it would be difficult to confirm the tertiary hypothesis.…”
Section: ˙=mentioning
confidence: 99%
“…In such a case, it is possible that there is a long-period third star in the system causing the periodic variations of their orbital periods. For example, Gies et al (2015) have found several detached eclipsing binaries in the Kepler field where the mass transfer process can be rejected due to their detached configurations, so a tertiary companion is the cause of the variations. However, if the orbital period of the third star is very long, it would be difficult to confirm the tertiary hypothesis.…”
Section: ˙=mentioning
confidence: 99%